Produksi Kalung Clay Handmade sebagai Peluang Usaha Kreatif Mahasiswa - Siti Magfirah Husain; Nadia Rahmawati Taufik; Siti Fawziah Novianty; Rahman Turani; Hariana (Jurnal Bisnis Digital & Perbankan, 2025)
Technopreneurship-based creative businesses are increasingly popular among students, especially in the production of handmade clay necklaces. This study aims to analyze the production process, cost calculation, and quality evaluation of handmade clay necklaces, as well as to explore effective marketing strategies through digital platforms. A descriptive qualitative approach was employed, collecting data through direct observation, in-depth interviews, and documentation of the production process over a two-month period. The findings indicate that handmade clay necklaces produced using clay and a “paku cumi” hook result in aesthetically appealing products, flexible in design, and with sufficient structural strength. The application of acrylic paint followed by a resin or varnish coating enhances visual quality and durability, although careful attention is required during the coloring and drying process to prevent uneven finishes or cracks. Cost analysis demonstrates that efficient material and tool usage reduces production expenses, allowing competitive pricing without compromising product quality. Evaluation of the process highlights the importance of accuracy in shaping, painting, and assembling to minimize defects and ensure customer satisfaction. This study contributes to the development of students’ creativity, practical skills, and technopreneurship capabilities while providing insights into combining digital marketing strategies with handmade craft production. The findings can support students in managing small-scale creative businesses efficiently and improving product competitiveness in the market.